EFFORTS TO IMPROVE UNDERSTANDING OF THE CONCEPT OF NUMBERS THROUGH THE MEDIA OF LEARNING NUMBERS CARDS IN EARLY CHILDREN IN RA BAETURROHMAH - Waadah, Siti Mala; Rukanda, Nandang (IKIP Siliwangi Bandung, 2025)
The background of this research is the learning process of understanding numbers in children, it appears that they do not understand simple concepts in everyday life, especially in the ability to recognize numbers, even though introducing the concept of numbers to children aged 5 years must use the right and appropriate methods and models in the learning process. accompanied by the right media. The purpose of the research is to find out efforts to improve understanding of the concept of numbers through the learning media of number cards in early childhood at RA Baeturrohmah. In this study, the researcher used a descriptive method with a qualitative approach where the sample consisted of one principal of RA Baeturrohmah, one teacher of RA Baeturrohmah, and eight students of RA Baeturrohmah. Data collection techniques are carried out to the respondents through interviews and observations.The result is that students can take part in learning to increase understanding of numbers with number card learning media where the process is carried out with students learning while playing so that students can follow the learning well. This can be seen from the observations of students experiencing an increase in understanding of numbers. So it can be concluded that learning media can help increase students' understanding of learning numbers in particular.Â Keywords: Early Childhood, Number Cards, Number Concepts, Learning Media